La Nostra Vita con Ezio e Ricordi di guerra - Aghib Levi D'Ancona, Flora (Biblioteca di storia, 2021)
Our life with Ezio and Memories of War, written by Flora Aghib Levi D'Ancona traces the life of her husband Ezio Levi, a Jewish Italian philologist and hispanist, their experiences of exile in the US where the couple fled after the racial laws. Completed with a historiographical introduction and an appendix of unpublished letters, the volume traces Ezio's path as a Jewish intellectual in Fascist Italy, his role as a cultural mediator of Spanish contemporary literature to Italy, the trauma of the racial laws, and the challenges of the American exile. Expression of a women's exile literature, the pages reflect the authors experience as a mother writing for her children left in Italy and of an intellectual Italian Jewish woman dealing with the challenges of exile and memory.